A comparative analysis between material extrusion and other additive manufacturing techniques: Defects, microstructure and corrosion behavior in nickel alloy 625. (January 2023) - Carrozza, A.; Lorenzi, S.; Carugo, F.; Fest-Santini, S.; Santini, M.; Marchese, G.; Barbieri, G.; Cognini, F.; Cabrini, M.; Pastore, T.
Graphical abstract: Highlights: MEX-processed alloy 625 provides spherical micro-pores and elongated macro-defects, dependent on the scanning strategy adopted. MicroCT analyses allowed to reconstruct the 3D structure of the macro-defects consisting in a continuous grid of interconnected hollow channels. The microstructure was characterized by γ-Ni grains and Mo-, Nb-, Si-rich precipitates. X-ray diffraction evidenced the presence of M6 C-type carbides. Core and contour had different responses to intergranular corrosion, due to the different shape and size of the secondary phase. Abstract: Additive manufacturing (AM) is becoming a consolidated reality for nickel alloys production in recent years. Among the several technologies available, material extrusion (MEX) is gaining industrial interest. However, its qualification is fundamental to achieve high-value applications. In this work, Ni alloy 625 produced using different AM techniques was comparatively analyzed in terms of process-related defects, microstructure and corrosion behavior. Specimens manufactured via MEX, laser powder bed fusion (PBF-LB), and directed energy deposition (DED-LB) were investigated. The MEX-produced samples showed micropores and periodically-arranged elongated macro-defects. These were analyzed in terms of image analysis and micro computed tomography. The resulting void 3D structure was mainly constituted by a grid of hollow channels, mimicking the ± 45° scanning strategy adopted. The microstructure was mainly constituted by Mo-, Nb- and Si-rich precipitates in a Ni matrix. The second phases had a blocky morphology in the core part of the material. Conversely, an elongated shape following the grain boundaries was detected in the contour. These microstructural variations impacted on the response of the alloy in an aggressive environment (ASTM G28-A). In fact, the core underwent a localized attack, whilst the contour part was characterized by a negligible effect, as assessed in the PBF-LB and DED-LB-processed specimens.